Linking flow and upper thermal limits of freshwater mussels to inform environmental flow benchmarks. (3rd September 2020) - Khan, Jennifer M.; Dudding, Jack; Hart, Michael; Robertson, Clinton R.; Lopez, Roel; Randklev, Charles R.
Abstract: Freshwater ecosystems are experiencing shifts in the natural range and variation of water temperatures due to anthropogenic activity, and these shifts can negatively affect survival, growth, and reproduction of aquatic species. Among the groups most affected are freshwater mussels of the family Unionidae. Knowledge of sublethal and lethal effects on mussels from changes in water temperature are largely unknown, especially for species from arid and semi‐arid regions such as the south‐western U.S.A. This limits the ability to assess, forecast, and adaptively manage this threat for those species and to understand how temperature influences population performance and community structure. To determine the effects of elevated water temperature on mussels from the south‐western U.S.A., we evaluated the upper thermal tolerances of adults of three species ( Amblema plicata, Cyclonaias necki, and Fusconaia mitchelli ) from the Guadalupe River. Mussels were acclimated to 27°C and then tested across a range of experimental temperatures (30–39°C) in standard acute (96‐hr) and chronic (10‐day) laboratory tests. The acute and chronic thresholds identified in thermal tolerance testing were then related to in situ water temperature and flows using a uniform continuous above‐threshold analysis, which evaluates the duration and frequency of continuous events above a specified temperature threshold. Median lethal temperature in 96‐hr tests averaged 36.4°C and ranged from 33.7 to 37.5°C, while the chronic 10‐day tests averaged 35.9°C and ranged from 32.4 to 37.5°C. Thermal tolerances of F. mitchelli were significantly lower than both A. plicata and C. necki, and the uniform continuous above‐threshold analysis showed that temperature affecting 5% of the population thresholds were exceeded for F. mitchelli in the Guadalupe River at both acute (96‐hr) and chronic (10‐day) values (30.5 and 28.4°C, respectively). Findings from this study indicate that freshwater mussels from the arid and semi‐arid regions of the south‐west U.S.A. are already at risk from rising environmental temperatures and altered hydrology. However, by incorporating laboratory thermal tolerance estimates with in situ temperature and discharge data, we provide a range of hydrologic thresholds to inform environmental flow recommendations and potentially mitigate thermal stress occurring during periods of low flow. In addition, this method can be readily adapted to other arid regions to guide flow recommendations or assess whether flow standards are sufficient to protect freshwater mussel populations during severe droughts and low flow periods.